PENGARUH BAHASA SLANG TERHADAP PROSES KOMUNIKASI MAHASISWA - Nelsa Dwi Mahela; Abdila Abel Mandev; Dhita Amelia; Lili Anggraini; Lupia Ainia Nur; Farel Olva Zuve (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research analyzes the influence of slang language on communication processes and the erosion of character values among students at Universitas Negeri Padang, specifically semesters five to eight. A qualitative descriptive approach involved thirty students through semi-structured interviews, campus observations, and analysis of two thousand four hundred fifty WhatsApp chat transcripts over two months. Results show eighty-seven percent of respondents use slang more than fifty times per day, dominated by "mantul" three hundred forty-two times, "cringe" two hundred thirty-four times, and "bego" one hundred eighty-seven times. Slang accelerates informal communication in ninety-two percent of peer cases but causes misunderstandings in sixty-four percent with lecturers. Likert scale scores for character average two point three, with declines in politeness and empathy due to negative slang. Findings confirm the duality of slang strengthening group solidarity yet eroding discipline. Recommendations include digital standard language workshops and WhatsApp ethics guidelines for faculties. Keywords: slang language, student communication, character values